Cloning and expression of the nucleoprotein gene (NP) of newcastle disease virus (NDV) in Escherichia coli for immunodiagnosis application - Silva, Ketherson Rodrigues [UNESP]; Costa Mello GonçAlves, Mariana [UNESP]; de Oliveira, Elisabete Schirato [UNESP]; Fernando, Filipe Santos [UNESP]; de Silva Montassier, Maria Fatima [UNESP]; Fernandes, Camila Cesario [UNESP]; de Feres Tamanine, Maria Lourdes [UNESP]; Borzi, Mariana Monezi [UNESP]; dos Santos, Romeu Moreira [UNESP]; de Mendonca, Andre Oliveira [UNESP]; Reischak, Dilmara [UNESP]; Paulillo, Antonio Carlos [UNESP]; et al. (My University, 2014)
The nucleocapsid protein (NP) of newcastle disease virus (NDV) is an important antigen to develop a serologic assay on account of its highly conserved sequences and high immunogenicity. This study aimed at expressing the gene of the NP of NDV in a heterologous system (Escherichia coli), using the appropriate vector. The NDV-NP protein was expressed as a fusion recombinant protein containing SUMO peptide and poly-histidine tags. This recombinant nucleocapsid protein (rNP) was expressed in a soluble form which was easily purified and showed the ability to react with chicken anti-NDV polyclonal antibodies. An indirect ELISA method based on the adsorption of an antigen composed by NP (rNP-NDV-ELISA) was developed. By comparing this rNP-NDV-ELISA with haemagglutination-inhibition test (HI) high and significant correlation with the HI (r = 0.83) was found. In addition to, high sensitivity (88.9%), specificity (95.5%), accuracy (90.4%) and agreement (0.85) were obtained. In conclusion the results indicated that the cloning and expression procedures used in this study provided a rNP that shared the major epitopes with the homologous viral protein and has the potential to be applied in ELISA for the immunodiagnosis of the important newcastle disease.
Keywords: Cloning of NDV-NP gene; ELISA; Expression; Immunodiagnosis Application; Newcastle disease virus; Recombinant nucleocapsid protein; SUMO